A Study of the Past and Present Towards the Direction of Social Work of the Catholic Church in Thailand - Suksamran, Nantapon; Chinnawong, Apichit; Pongprasertsin, Saranyu; Kitcharoen, Aphisit; Lerttanongsak, Wittaya; Gais, Francis; Ongnawa, Wutthichai (Saengtham College Journal, 2025)
A Study of the Past and Present Towards the Direction of Social Work of the Catholic Church in Thailand. To study the current situation and needs of social work in the Catholic Church in Thailand. To create a vision for the future of social work in the Catholic Church in Thailand. Methodology: Phase 1: A survey was conducted with 245 respondents from 11 dioceses in Thailand. The respondents included policymakers, social development workers, stakeholders, laity, and people involved in social development networks. And Phase 2: A focus group discussion was conducted with 9 experienced social workers from 11 dioceses in Thailand. Findings: Phase 1: The majority of respondents were male (54.2%). Most respondents were lay consecrated persons (87.9%). The most prominent area of social work was relief and welfare (60.2%). The average score for the implementation of social work in five areas was between 3.47 and 4.42, which is considered high to very high. The highest average score for the pinion on the direction of social work was for the need to increase networking and collaboration (44.60%). The most suggested additional activities for the social work department were: Providing education on the social teachings of the Church. Empowering people with necessary skills. Coordinating and integrating work to help the poor. Providing scholarships for living. Encouraging community members to participate in finding solutions. Phase 2: The Catholic Church plays an important role in helping Thai society through various social works. The focus is on sustainable development, taking into account human dignity and values. The challenge is to work quickly and focus on activities, which may neglect long-term results. The Church must adhere to its teachings and strive for cooperation with all sectors. Future Directions: Focus on exchange and learning. Develop sustainable area-based projects. Emphasize values and human dignity. Evaluate results based on sustainability, impact on individuals and communities, and attitude change. Utilize the following guidelines: Emphasize spirituality. Integrate. Focus on sustainable projects. Develop sustainable communities.